2023
DOI: 10.18502/ijm.v15i1.11931
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of herpes simplex viruses types 1 and 2 infections among suspected children of encephalitis in Kermanshah, Iran

Abstract: Background and Objectives: Various infectious and non-infectious factors can cause encephalitis in the central nervous system (CNS), the most important of which are viruses. Herpes viruses are one of the most important causes of encephalitis worldwide. PCR detected the virus on the cerebrospinal fluid (CSF) sample. The aim of this study was to set up an in-house PCR to identify herpes simplex virus type 1 (HSV-1) and herpes simplex virus type 2 (HSV-2) and determine the prevalence of these viruses in suspected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Vilhelmova-Ilieva et al showed that the cell free supernatant of L. fermentum had a potent antiviral effect when it was in contact with HSV-1 for one hour ( 25 ). Elebeedy et al demonstrated a significant decrease in HSV-1 titer (1.25 log 10 TCID 50 /ml) using the L. acidophilus supernatant ( 26 ). Similarly, in the present study, the metabolites of L. reuteri reduced HSV-1 titer by 1.83 Log 10 TCID 50 /ml; therefore the supernatant of L. reuteri , like other mentioned Lactobacilli , contains anti-herpes virus compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Vilhelmova-Ilieva et al showed that the cell free supernatant of L. fermentum had a potent antiviral effect when it was in contact with HSV-1 for one hour ( 25 ). Elebeedy et al demonstrated a significant decrease in HSV-1 titer (1.25 log 10 TCID 50 /ml) using the L. acidophilus supernatant ( 26 ). Similarly, in the present study, the metabolites of L. reuteri reduced HSV-1 titer by 1.83 Log 10 TCID 50 /ml; therefore the supernatant of L. reuteri , like other mentioned Lactobacilli , contains anti-herpes virus compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The wide spectrum of clinical presentations of herpetic encephalitis, coupled with primary symptoms like fever, headaches, fatigue, and vomiting that are often nonspecific, complicates the diagnosis. Only 38% of non-neonatal children manifest with neurological symptoms such as seizures, which can facilitate earlier detection 11 , 18 . The case under discussion involves an infant presenting with acute onset seizures and fever.…”
Section: Discussionmentioning
confidence: 99%